Peripheral and central effects of NADPH oxidase inhibitor, mitoapocynin, in a rat model of diisopropylfluorophosphate (DFP) toxicity - Meyer, Christina; Rao, Nikhil S.; Vasanthi, Suraj S.; Pereira, Beatriz; Gage, Meghan; Putra, Marson; Holtkamp, Claire; Huss, Joselyn; Thippeswamy, Thimmasettappa (Frontiers in Cellular Neuroscience, 2023)
Organophosphates (OP) are highly toxic chemical nerve agents that have been used in chemical warfare. Currently, there are no effective medical countermeasures (MCMs) that mitigate the chronic effects of OP exposure. Oxidative stress is a key mechanism underlying OP-induced cell death and inflammation in the peripheral and central nervous systems that is not mitigated by the available MCMs. NADPH oxidase (NOX) is one of the leading producers of reactive oxygen species (ROS) following status epilepticus (SE). In this study, we tested the efficacy of the mitochondrial-targeted NOX inhibitor, mitoapocynin (MPO) (10 mg/kg, oral), in a rat diisopropylfluorophosphate (DFP) model of OP toxicity. In DFP-exposed animals, MPO decreased oxidative stress markers nitrite, ROS, and GSSG in the serum. Additionally, MPO significantly reduced proinflammatory cytokines IL-1β, IL-6, and TNFα post DFP exposure. There was a significant increase in GP91phox 29 , a NOX2 subunit, in the brains of DFP-exposed animals one-week post challenge. However, MPO treatment did not affect NOX2 expression in the brain. Neurodegeneration (NeuN and FJB) and gliosis [microglia (IBA1 and CD68), and astroglia (GFAP and C3)] quantification revealed a significant increase in neurodegeneration and gliosis after DFP-exposure. A marginal reduction in microglial cells and C3 colocalization with GFAP in DFP+MPO was observed. The MPO dosing regimen used in this study at 10 mg/kg did not affect microglial CD68 expression, astroglial count, or neurodegeneration. MPO reduced DFP-induced oxidative stress and inflammation markers in the serum, but only marginally mitigated the effects in the brain. Dose optimization studies are required to determine the effective dose of MPO to mitigate DFP-induced changes in the brain.